(untitled) (Faculty of Education Scientific Journal, 2024)
In this work we focused on the studying of even – even nuclei forms for .The study of deformation parameter derived from the reduced electric transition probability for transitions, and distortion parameter is calculated from intrinsic electric quadrupole moment .The relationship between two deformation parameters . and neutron magic number was studied through plotting the deformation parameters as a function of neutrons number. The results show that the deformation parameters and intrinsic electric quadrupole moment of nucleus decreased when the neutrons number approaches to magic number. In the present work, another relationship was studied; this was getting the ratio of . In this paper also the major and the minor ellipsoid axis were calculated, and the different between them have been determined.